Functional Outcome of Percutaneous K-wiring vs Closed Reduction and Plaster Casting in Treatment of Unstable Distal Radius Fractures: A Comparative Study - R Sahaya Jose; M Syed Moosa; N Kattu Bava (Journal of Orthopedics and Joint Surgery)
Introduction: Fractures in the distal end of the radius are one of the most common fractures treated by orthopedic surgeons, constituting nearly 18% of all fractures. Displaced, unstable distal end of radius fractures remain a challenging problem for orthopedic surgeons; they tend to heal with malunion if not treated properly. These fractures result in significant anatomic deformity and functional disability if the radial length and angulation are not maintained well in the course of treatment. The purpose of this study is to assess and compare the functional outcome of displaced distal end of radius fractures treated with closed reduction and percutaneous K-wiring vs the conventional method of closed reduction with plaster cast immobilization using the disability of arm, shoulder, and hand (DASH) score. Subjects and methods: A prospective comparative study was conducted among 50 patients who presented to the emergency medicine department and to the orthopedics outpatient department (OPD) at our tertiary care center from July 2022 to October 2023. Patients who had unstable closed distal radius fractures (DRFs), with patient age ranging from 18 to 80 years, and simple extra-articular DRFs (A2, A3), were included in the study. Patients with open fractures, intra-articular DRFs (A1, B, C), neurovascular injuries, pathological fractures, and previous history of distal radius fracture were excluded from the study. A total of 50 patients were divided randomly into two groups, with each group containing 25 patients. One group underwent closed reduction and percutaneous K-wiring, and the other group underwent closed reduction with plaster cast immobilization. Both groups of patients were followed up at the 1st, 3rd, and 6th week. At this stage, fracture union was confirmed radiologically and patients were encouraged to begin wrist movements. Thereafter, both groups of patients were regularly followed up at the 9th, 12th, and 24th week, and at 1 year, and their functional outcome was assessed using the DASH score, Lindstrom grading, and Frykman grading. Statistical analysis used: The data were analyzed using SPSS software version 25.0. Continuous variables were expressed as mean ± standard deviation (SD), and categorical variables were expressed as frequencies and percentages. The Mann–Whitney U test was used to compare the DASH scores between the two groups. The Chi-squared test was used to compare categorical variables. A p-value of <0.05 was considered statistically significant. Results: The average DASH score at 9 weeks was 54 and 68 in the K-wire and cast immobilization groups, respectively. The DASH score was assessed at 9, 12, and 24 weeks in both groups. The Mann–Whitney U test was used to assess the functional outcome. The mean DASH score among the groups, though showing a minor difference (DASH score higher in those with cast immobilization), was not statistically significant. At the end of 9, 12, and 24 weeks, the p-value was 0.059, 0.094, and 0.253, respectively. The postoperative radiological assessment showed a significant difference in both the K-wire fixation and cast immobilization groups. The anatomical outcome was assessed according to Lindstrom and Frykman's criteria. In the K-wire fixation group, 48% had grade I, 40% had grade II, and 12% had grade III outcomes. In the cast immobilization group, an equal proportion (40%) had grade I and grade II, 12% had grade III, and 8% had grade IV outcomes. Conclusion: The results showed that both treatment modalities had significant improvements in radiological and anatomical parameters. However, patients treated with K-wire fixation generally exhibited better functional outcomes, as indicated by lower DASH scores, improved range of motion, and fewer complications such as stiffness and moderate pain. Although the differences were not always statistically significant, the trends suggest that K-wire fixation might offer a slight advantage in terms of overall functional recovery.